"Arbequina" Olive Oil Composition Is Affected by the Application of Regulated Deficit Irrigation during Pit Hardening Stage. (18th February 2020) - Sánchez‐Rodríguez, Lucía; Kranjac, Marina; Marijanović, Zvonimir; Jerković, Igor; Pérez‐López, David; Carbonell‐Barrachina, Ángel A.; Hernández, Francisca; Sendra, Esther
Abstract: Three new regulated deficit irrigation (RDI) treatments were applied to "Arbequina" olive orchards during pit hardening. Oil quality was determined by measuring analytical parameters for olive oil grading, antioxidant activity, total phenol content, fatty acid profile, volatile compounds profile, and sensory analysis. Oils from RDI were classified as "extra virgin olive oil" and their quality was improved due to their higher antioxidant potential (ABTS + [increased 75%] and DPPH ˙ [increased 25%] assays) and phenols (increased 53%) than control. Concentration of total volatile compounds decreased ( 27%) but RDI olive oils showed a more balanced profile (alcohols, aldehydes, and esters). Monounsaturated fatty acid content increased ( 5%) and atherogenic and thrombogenic indexes decreased ( 8.5%) in RDI olive oil. Regarding sensory analysis, RDI provided more balanced oils with higher fruit aroma than control. Other benefits of RDI olive oil, when compared with oil from full irrigated orchards are reduced use of water and improved functional and sensory quality.